Cardiovascular risk factors in Chinese women with a history of gestational diabetes mellitus - Mai, Caiyuan (Int J Clin Exp Med, 2015)
Background: Women with a history of gestational diabetes (GDM) are at increased risk of developing cardiovascular diseases compared with normal women. This study aimed to evaluate the cardiovascular risk factors in Chinese women with GDM. Methods: 453 women with GDM (cases) and 1,180 healthy women (controls) were included in this study. The post-partum examinations included 2 h 75 g oral glucose tolerance tests, lipid profiles, anthropometric measurements (blood pressure, height, weight) and documentation of medical history, diet, and lifestyle. Results: Compared with controls, the risks of abnormal glucose metabolism, obesity, hypertension, metabolic syndrome in women with a history of GDM were 4.61, 1.30, 1.57 and 3.52, respectively. Fasting blood glucose, progestational body mass index (pBMI) and antenatal insulin resistance at antenatal visit were predictors for abnormal glucose metabolism. pBMI and antenatal diastolic blood pressure were predictors for hypertension. pBMI and weight gain during pregnancy were predictors for obesity/overweight. pBMI, antenatal systolic blood pressure and antenatal triglyceride were predictors for metabolic syndrome. Conclusions: Women with a history of GDM have increased rates of cardiovascular disease risk factors including abnormal glucose metabolism, obesity, hypertension, metabolic syndrome. pBMI is the common independent predictors of cardiometabolic disease in the post-partum.